The effect of disgust-eliciting media portrayals on outgroup dehumanization and support of deportation in a Norwegian sample. (July 2015) - Dalsklev, Madeleine; Kunst, Jonas Rønningsdalen
Abstract: Public discourse regarding the Roma has been heated in many western European countries. This study investigates whether feelings of disgust, elicited through negative media portrayals, can lead to more dehumanization and support of deportation toward this minority. While Study 1 ( N  = 30) validated a measure of dehumanization in the Norwegian context, Study 2 ( N  = 195) experimentally tested whether disgust-eliciting media portrayals would increase dehumanization tendencies on this validated measure and support of deportation toward the Roma. As expected, reading a newspaper article focusing on allegedly low hygienic standards among the Roma increased the feeling of disgust, which, in turn, led to higher degrees of dehumanization and support of deportation. While being the first study experimentally showing that disgust leads to dehumanization of a real societal minority group, the results also have important implications for how media discusses and presents social issues regarding devalued minority groups.